Necrotizing Fasciitis Caused by Gas-producing Methicillin-sensitive Staphylococcus aureus: A Case Report - Travis S. Bullock; Zachary Jodoin; Samuel S. Ornell; Nicolas A. Morton-Gonzaba; Ravi A. Karia; Case W. Martin (Journal of Orthopaedic Case Reports)
Introduction: It is well known that diabetic patients have impaired wound healing, increased susceptibility to infection, and harbor tissue that supports the growth of gas-producing infections. Necrotizing fasciitis (NF) is an uncommon soft-tissue infection characterized by extensive necrosis of subcutaneous tissue and fascia with relative sparing of the skin and muscle tissues. The majority of gas-producing infections are polymicrobial in nature, and therefore, NF with Staphylococcus aureus as a single etiologic agent is exceedingly uncommon. Case Report: This is a case of a 46-year-old male that developed gas-forming NF and abscesses from methicillin-sensitive S. aureus (MSSA) after a complicated course involving undiagnosed type 2 diabetes mellitus (T2DM), diabetic ketoacidosis, and bacteremia. The disease course presented relatively slowly with mild systemic symptoms, knee pain, erythema, and edema, but steadily progressed over days leading to an elevated level of care. Multidisciplinary care was necessary to treat the patient, including surgical and intravenous antibiotic therapies. The patient’s care was prolonged due to decreased patient compliance with recommended therapies and difficulty with appropriate shared decision-making. Conclusion: Although NF caused by monomicrobial infection with methicillin-resistant S. aureus has been previously reported, awareness of this condition remains limited, especially with concomitant gas formation. Physicians should have a high index of suspicion for NF with MSSA as a potential etiologic agent when treating patients with symptoms of a necrotizing soft-tissue infection, particularly those with underlying T2DM or a history of recent needle puncture. By engaging in shared decision making, health outcomes in these serious infections can be optimized.